2021
DOI: 10.1098/rsfs.2021.0039
|View full text |Cite
|
Sign up to set email alerts
|

Porous surfaces: stability and recovery of coronaviruses

Abstract: The role of indirect contact in the transmission of SARS-CoV-2 is not clear. SARS-CoV-2 persists on dry surfaces for hours to days; published studies have largely focused on hard surfaces with less research being conducted on different porous surfaces, such as textiles. Understanding the potential risks of indirect transmission of COVID-19 is useful for settings where there is close contact with textiles, including healthcare, manufacturing and retail environments. This article aims to review current research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…Differences in virus survival between these materials have not been precisely demonstrated in the literature. However, some studies indicated that virus survivability on surfaces may depend on several virus-surface interactions, including hydrophobicity and electrostatic attraction, which depend on pH, virus surface charge concentration, and isoelectric properties of surface proteins ( Dika et al, 2013 , Fuhs et al, 1985 , Owen et al, 2022 ). Among the food-contact surfaces commonly used in the food industry, there are porous surfaces like paper, wood, and fabric; additionally, other non-porous surfaces are also used.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in virus survival between these materials have not been precisely demonstrated in the literature. However, some studies indicated that virus survivability on surfaces may depend on several virus-surface interactions, including hydrophobicity and electrostatic attraction, which depend on pH, virus surface charge concentration, and isoelectric properties of surface proteins ( Dika et al, 2013 , Fuhs et al, 1985 , Owen et al, 2022 ). Among the food-contact surfaces commonly used in the food industry, there are porous surfaces like paper, wood, and fabric; additionally, other non-porous surfaces are also used.…”
Section: Discussionmentioning
confidence: 99%
“…No viable virus was recovered under any tested condition. While this issue has been observed, to variable degrees, in multiple other reports [ 35 , 36 , 37 , 38 , 39 ], in order to have high confidence in any neutralization/decontamination protocol to be used on live animals, further work is necessary to optimize recovery from this difficult surface. It is also important to note that fur on live animals is likely maintained at a higher temperature than the ambient air, and that this difference could and should be implemented in future laboratory testing.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that dryness accelerates the inactivation of SARS‐CoV‐2 on paper and other porous solids; conversely, droplets of water remaining on waterproof surfaces protects the virus from dryness. 54 , 67 Experimental studies show that the stability of SARS‐CoV‐2 on surfaces is also affected by its surrounding matrix; the suspending medium used to dry the virus onto surfaces is another important factor influencing survival times. 53 , 68 Several studies have demonstrated that the addition of a moderate amount of protein, like bovine serum albumin or mucus, to the inoculating suspension when loading onto a surface increases SARS‐CoV‐2 infectivity, indicating that additional protein provides a protective effect for the virus during and after drying on surfaces.…”
Section: Viability and Stability Of Sars‐cov‐2 In The Environmentmentioning
confidence: 99%
“…It is hypothesized that dryness accelerates the inactivation of SARS‐CoV‐2 on paper and other porous solids; conversely, droplets of water remaining on waterproof surfaces protects the virus from dryness. 54 , 67 …”
Section: Viability and Stability Of Sars‐cov‐2 In The Environmentmentioning
confidence: 99%